Touchscreen Archaeology Tracing Histories of Hands-On Media Practices - Strauven, Wanda (meson press, 2021)
The touchscreen belongs to a century-long history of hands-on media practices and touchable art objects. This media-archaeological excavation examines the nature of our sensual involvement with media and invites the reader to think about the touchscreen beyond its technological implications. In six chapters, the book questions and historicizes both aspects of the touchscreen, considering "touch" as a media practice and "screen" as a touchable object.